IDENTIFICATION OF CORONARY ATHEROSCLEROTIC LESIONS IN RAT INDUCED BY INTRAVENOUS CANDIDA ALBICANS - Prasetya, Rendra Chriestedy; Fatimatuzzahro, Nadie; Ayu Susilawati, I Dewa; Yonenda, Ayu Prativia (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aimed to identify the sign of coronary atherosclerosis lesion in rat induced by intravenous Candida albicans. Methods: This research was an experimental laboratories (in vivo) that used 15 male Wistar rat, divided into three groups of the control, the first treatment group injected by C. albicans intravenously with concentration of the 10âˆ’10 cells/mL and the second treatment group injected by C. albicans intravenously with concentration of the 10âˆ’12 cells/mL. 0.2 mL of C. albicans were injected to the first and second treatment group on 1st, 4th, 9th, 16th, and 23rd day. On the 5th week, rats were sacrificed, taken its hearts that contained the coronary artery. Rat's heart had been fixed; histological preparations were made and painted with Picrosirius Red and Sudan IV, observed by a microscope. Results: The artery walls of the first and second treatment group were thicker than the control group. Lesions and disposition lipids of the first and second treatment group were more frequent than the control group. Conclusion: Intravenous C. albicans can increase the risk of coronary atherosclerosis.